Влияние 1α-оксивитамина D₃ и 24,25-диоксивитамина D₃ на пул свободных аминокислот и другие показатели сыворотки крови цыплят - Бондаренко, Л.Б.; Яхимович, Р.И.; Бауман, В.К. (Биополимеры и клетка, 1993)
Comparative investigation of vitamin D₃, lαOH D₃ and 24, 25(OH)₂D₃ antirachitic activities and their abilities to lower cholesterol levels and to change pool of free aminoacids in serum was carried out in experiments on chickens. Though vitamin D₃ and its derivatives effects were similar by characters, but they differed markedly in dependence of dose and chemical structure of compounds. lαOHD₃ had the greatest effect on these indices. Introduction of OH-group in C-24, instead of C-l, caused the lowering of vitamin D₃ derivative ability to regulate Ca and Pn metabolism and increasing to influence on cholesterol metabolism.